In‐hospital mortality and length of stay of patients with hypertensive crisis treated at public hospitals in Harari Regional State, Eastern Ethiopia - Natanim Degefu; Dumessa Edessa; Melaku Getachew; Aboma Motuma; Lemma Demissie Regassa (The Journal of Clinical Hypertension, 2023)
Abstract Hypertensive crisis poses substantial cardiovascular morbidity and mortality. This study aimed to assess in‐hospital mortality, length of stay (LOS), and their predictors among patients with hypertensive crisis treated at public hospitals in Harari Regional State, Eastern Ethiopia. An institutional‐based retrospective cohort study was conducted from October 1 to 31, 2022. The medical records of 328 patients with hypertensive crisis treated at two public hospitals between September 1, 2017 and August 31, 2022 were reviewed. Cox proportional hazards regression and negative binomial regression were used to identify predictors of in‐hospital mortality and LOS, respectively. The in‐hospital mortality rate of patients with hypertensive crisis was 18.94 (95% confidence interval (CI): 12.08–29.70) per 1000 person‐day observation. The median (interquartile range) LOS of these patients was 10 (4–120) hours. Age ≥65 years (adjusted hazard ratio (AHR): 3.30; 95% CI: 1.17– 9.33); increment in initial systolic blood pressure (AHR: 1.040; 95% CI: 1.014–1.066); and having acute brain‐related damage (AHR: 4.02; 95% CI: 1.48–10.88) were predictors of in‐hospital mortality. Rural residence (adjusted incident‐rate ratio (IRR): 1.34; 95% CI: 1.03–1.75); having a history of medication discontinuation (adjusted IRR: 1.59; 95% CI: 1.16–2.18); comorbidity (adjusted IRR: 1.90; 95% CI: 1.49–2.43); acute brain‐related damage (adjusted IRR: 13.32; 95% CI: 9.22–19.24), acute cardiac‐related damage (adjusted IRR: 7.40; 95% CI: 4.90–11.16); and acute kidney injury (adjusted IRR: 7.64; 95% CI: 5.46–10.69) were predictors of LOS. Thus, it is necessary to develop strategies that allow early screening and follow‐up of patients at risk.